Strategy for Evaluation of Quality Assurance System Implementation Policies in Increasing the Competitiveness of Private Universities in the City of Bandung - Agus Supriatna; Benyamin Harits; Yaya Mulyana Abdul Azis (Doctoral Program of Social Science Pasundan University, 2023)
The implementation of the Quality Assurance System for Private Universities in the City of Bandung is currently still not effective, in the sense that the implementation of the quality assurance system is not fully in accordance with the quality instruments set by the government. The focus of this research is Policy Evaluation in the implementation of the Quality Assurance System for Private Higher Education in the City of Bandung. The sub-focus of this research is the dimensions that need to be carried out in evaluating quality assurance system implementation policies, namely: administrative evaluation, judicial evaluation and political evaluation. This research uses a qualitative descriptive analysis method and is supported by the SWOT technique. This was chosen with the consideration that actual data can be obtained, being able to study the research problem in depth so that results can be obtained that are in line with expectations. The results of the research show that the implementation of the Quality Assurance System for Private Higher Education in the City of Bandung is still not effective, so policy evaluation is needed through (1) Administrative evaluation taking into account: Effort Evaluation, Performance Evaluation, Adequacy of Performance, Efficiency Evaluation and Process Evaluation, (2) Judicial evaluation by paying attention to: Issues of legal validity, Possible Violations of the Constitution, Possible Violations of the Legal System, Possible Violations of Ethics and State Administration Rules, (3) Political evaluation by paying attention to: Political Process in determining policies, Acceptance of political constituents towards public policies, Implementation Information Technology. The results of the policy evaluation in this research then produced a recommendation strategy regarding the implementation of a higher education quality assurance system that is in accordance with government standards.